ترجمه هاى تكرارى وعوامل ظهور آن Repeated Translations and the factors that Affect their Appearance (Journal of the College of Languages (JCL), 2017)
Abstract My research dealt with the phenomenon of repeated translation.First Section deals with identifying repeated translation from both linguistic and terminological sides . Section two display the reasons and factors that stand behind this phenomenon while section three sheds light on the positive and negative sides of the phenomenon understudy and in the last section , the researcher sets several recommendations which lead to prevent the widespread of repeated translation phenomenon . چکیده این بحث که با عنوان (ترجمه های تکراری وعوامل ظهور آن ) پدیدهء ترجمه های تکراری را از جنبه های متعدد مورد بحث وبررسی قرار داده است, واز چهار مبحث تشکیل شده است, به ترتيب زیر است: مبحث يكم واژهء تكرار را ىر اصطلاح ولغت مورد تعریف قرار داده است. ومبحث دوم به اسباب وعواملی که باعث بوجود آوردن آن پدیده اختصاص شده است. در مبحث سوم پژوهشگر تا حد امکان جنبه هاى مثبت ومنفي پدیدهء ترجمه های تکراری را بیان نمود. در پایان وضمن مبحث چهارم پژوهشگر پیشنهادهائی متعددی را برای جلوگیری پدیدهء ترجمه های تکراری را ایراد نمود. از جملهء نتایجی که پژوهشگر به آن رسید این است که مترجم باید در هنگام ترجمهء کتاب امین ودقیق باشد,وسعی میکند ترجمهء خوبی وخالی از اشتباهات ارائه کند,وگرنه اشتباهات او بهانه ای برای مترجمان دیگر تا دست به ترجمهء مجدد آن کتاب خواهد بود. ونیز دولت باید از مترجمان حمایت وپشتبانی بکند,تا بتوانند ترجمه های خوبی ارائه کنند. عوامل دیگر که به وجود آوردن چنین ترجمه ها دريافت برخى از آثار ادبى يا علمى به جايزه هاى بين المللى است که این امر باعث می شود که مترجمان وناشران به ترجمه ونشر آن اثر شتاب ميىزدند.AbstractThe results of this research show that the translator should be precise ,honest, skillful and has a high scientific morality in order not to let his mistakes be a reason for other translators to translate the same book another time ;Each state should join at least one of the international organizations which defend the publishing and author rights and that if one of the scientists gains one of innovation prices , this will consider one of the most important reasons that stands behind the appearance of this phenomenon . that's why we see the translators repeat the translation of translated books in order to gain money and fame . Keywords: Translation, duplicate, factors, appearance, suggestion